Efficacy and safety of COVID-19 vaccines for patients with spinal tumors receiving denosumab treatment: An initial real−clinical experience study - Wang, Pengru; Li, Bo; Zhou, Shangbin; Xin, Yingye; Zhu, Zhipeng; Duan, Shujie; Bai, Danyang; Yuan, Hao; Xu, Wei; Xiao, Jianru (Frontiers in Oncology, 2023)
Background Even if COVID-19 vaccine has gradually been adopted in the world, information of side effects and crosstalk in patients with spinal tumors is absent due to the exclusion from clinical research. In this research, we aimed to investigate the efficacy and safety for the patients with spinal tumors treated by denosumab. Methods In this retrospective research, 400 patients under treatment of denosumab against spinal tumors in real-clinical experience were grouped into two cohorts according to the treatment of COVID-19 vaccine. And linked hospital data, serum samples and unsolicited related adverse events had been collected from January 22nd 2021 to June 1st 2021 respectively. Results 233 patients of all participants who received regular treatment of denosumab were vaccinated by mRNA or inactivated vaccine. Patients of metastatic disease and primary osseous spinal tumor showed similar distribution in both two groups. Over the study period, within 176 patients tested the status of serologic response of vaccine, 88(81.48%) and 41(87.23%) individuals injected one or two inactivated vaccines had effective antibody against SARS-CoV-2 infections. As 21 patients (85.71%) treated by mRNA vaccine did. Considering of the safety of vaccine, most common systemic adverse events were nausea or vomiting (45 events vs 23events). Interestingly, fewer participants in the vaccine group were statistically recorded in local adverse events than in the placebo group (16 events vs 33 events). Conclusions Our initial real-clinical experience suggests that COVID-19 vaccines are likely safe and effective in in patients with spinal tumors receiving denosumab treatment.